運用RAR 英文教學策略以達成有效教學 Implementation of the RAR English Teaching Strategy to Achieve Instructional Effectiveness - 呂正雄 Lu, Cheng-Hsiung (National Changhua University of Education, 2009)
本研究在於暸解學生過去的英文學習經驗，以及RAR 英文教學策略能否在教學現場，達成有效教學的目的。在65 位學生參與，長達一年的實證教學情況下，本研究之結論如下： 1.學生英文的學習經驗可分成三階段：(1)小學階段的快樂型學習，(2)國、高中階段的石磨式的痛苦學習，以及(3)大學階段的高飛型愉悅學習、茫然型不知何去何從的學習、或者沈淪式的放棄學習。 2.教師生活經驗可作為設計英文教材的源由構想。 3.課堂給予學生實作英文學習活動，能讓學生的學習態度變成積極參與，而不是被動接受。 4.配合教學科技呈現圖片影像，能激勵學生的學習興趣。 5.藉由學生的回饋意見，修正教學策略，並達到「雙重回饋」之效應。 6.RAR 英文教學策略促進師生互動，而學生對英文學習亦表現正面肯定的態度。 The purposes of this study were twofold: (1) to understand my students' previous English learning experiences, and (2) to examine whether the established RAR English teaching strategy could fulfill the instructional effectiveness in the empirical teaching settings. The action research method was adopted to fulfill the needs of this study, and the conclusions of the study were summarized as follows: 1.Three phases existed with my students' English learning experiences: (1) merry-go-round at the elementary school level, (2) back-to-the-grind at the junior and senior high school level, and (3) flying-over-the-sky, to-be/not-to-be, or crash-to-the-ground at the university level. 2.Lived experiences of the teacher could be utilized as the rationale for designing English teaching materials. 3.Assignments in the class provided students with hands-on English learning activities, and facilitated them to become active participants, rather than silent recipients. 4.Students were motivated to learn the contents by showing them photographs with the assistance of instructional technological equipment. 5.Students' reflective journals enabled me to revise my teaching strategies and to achieve the "double-feedback" effect. 6.With the RAR English teaching strategy, the interaction between students and me was satisfactory, and students expressed positive attitudes toward English learning.